Geographic Differences in Childhood Overweight, Physical Activity, Nutrition and Neighbourhood Facilities: Implications for Prevention - Simen-Kapeu, Aline (Can J Public Health, 2010)
BACKGROUND: Childhood overweight is a major public health concern. Whereas various studies have documented higher prevalence rates in rural areas compared to urban areas, little is known about what is causing these differences. We sought to identify the factors underlying the overweight differentials by examining physical activity and nutrition behaviours as well as neighbourhood characteristics of urban areas, towns and rural areas across Alberta. METHODS: In 2008, we surveyed 3,421 grade five students and their parents from 148 randomly selected schools. Students completed the Harvard Food Frequency Questionnaire, questions on physical activities, and had their height and weight measured. Parents completed questions on socio-economic background, child’s lifestyle, and neighbourhood perception. We applied multilevel regression methods to quantify the geographic differentials in physical activity, nutrition and neighbourhood facilities. RESULTS: The prevalence of overweight was 28.5% among Albertan grade five students, with 6.7% being obese. Among students attending schools in towns and rural areas, the prevalence of overweight (obesity) was 29.8% (7.9%) and 30.6% (8.0%), respectively. Compared with students attending urban schools, those attending schools in towns and rural areas reported more physical activity despite perceiving less access to playgrounds/parks and recreational programs (p<0.01). These latter students further reported poorer diets and purchasing more energy-dense foods and snacks at their schools (p<0.01). CONCLUSION: Our findings confirmed the existence of geographic differentials in overweight and its underlying causes. The study urges more promotion of healthy eating and active living, particularly in towns and rural areas to reduce geographic inequalities in health.